2017
DOI: 10.1111/jns.12239
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Guillain‐Barré syndrome in Finland 2004–2014

Abstract: At total mean incidence of 0.84-1.1/100,000 the occurrence of Guillain-Barré syndrome (GBS) is reported to be low in Finland compared to other Caucasian populations. However, a recent study from Southwestern Finland reported an incidence of 1.82/100,000 which is comparable to other Caucasian populations. We analyzed discharge data covering the years 2004 through 2014 on all neurological admissions in all Finnish university and central hospitals with a primary diagnosis of GBS. A total of 989 admissions due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
30
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 27 publications
(49 reference statements)
15
30
2
3
Order By: Relevance
“…A 10-year study showed that 2.1/100,000 acute paralysis cases were GBS, of which the male-to-female ratio was 1.5:1 24. Furthermore, the incidence of GBS among males increased by 28% and among women increased by 14%, for every 10-year increment of age 24. Findings in this setting were similar to previous studies that showed a higher incidence among males 4,30…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A 10-year study showed that 2.1/100,000 acute paralysis cases were GBS, of which the male-to-female ratio was 1.5:1 24. Furthermore, the incidence of GBS among males increased by 28% and among women increased by 14%, for every 10-year increment of age 24. Findings in this setting were similar to previous studies that showed a higher incidence among males 4,30…”
Section: Discussionsupporting
confidence: 87%
“…The average age of children who complained of GBS in this setting was 8.59±4.99 years, which was slightly higher than that reported in the literature 28. A 10-year study showed that 2.1/100,000 acute paralysis cases were GBS, of which the male-to-female ratio was 1.5:1 24. Furthermore, the incidence of GBS among males increased by 28% and among women increased by 14%, for every 10-year increment of age 24.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Because of this, it is likely that GBS is more easily detected in Korea, which has relatively good health accessibility given the universal health insurance system operated by the government [35]. The incidence ratio of males to females in this study (1.5) is similar to the ratio of 1.8 reported in previous studies [36]. Male predominance in the incidence of GBS is a well-known phenomenon, but the cause is still unclear [11].…”
Section: Discussionsupporting
confidence: 80%
“…Worldwide, Guillain–Barré syndrome (GBS), also known as acute inflammatory demyelinating polyradiculoneuropathy, is a neurological condition that can occur in otherwise healthy adults and at any age, with a reported incidence of 1–4 per 100,000 individuals. 1 , 2 Owing to the improvements in the diagnosis of GBS, the disease has been shown to have an increasing incidence rate. 3 , 4 Also, although immunoglobulin and plasma therapy have shortened the recovery time for the GBS, patients with GBS still have a mortality rate of 2%–8%, and ~20% of patients with GBS will not recover completely, but will have long-term neurological sequelae.…”
Section: Introductionmentioning
confidence: 99%